2022
DOI: 10.21009/hayula.006.01.07
|View full text |Cite
|
Sign up to set email alerts
|

The Commodification of Religion in The 2012 Regional Election of Purwakarta Regency

Abstract: This study aims to describe the involvement of religious instruments in the dynamics of the 2012 Regional Head Elections for the Regent and Deputy Regent of Purwakarta Regency. This study uses a qualitative method with the dramaturgical approach of Erving Goffman on symbolic interactionism and Max Weber on social action theory. This study indicates that the normative use of religious elements is used as a weapon for candidates as a political commodity to attract mass sympathy and highlight the identity of a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Examination using an electron microscope some time after exposure to cysteine proteinase in the worm Heligmosomoides bakeri, showed that the outer layer of the cuticle began to wrinkle and lose its rigidity, and over time it shrank. Bromelain enzyme is a protease enzyme which has the same working power as renin (renet), papain and fisin which has the property of hydrolyzing proteins [5]. Hydrolysis that occurs with protease enzymes is caused by breaking peptide bonds from substrate bonds [10].…”
Section: Introductionmentioning
confidence: 99%
“…Examination using an electron microscope some time after exposure to cysteine proteinase in the worm Heligmosomoides bakeri, showed that the outer layer of the cuticle began to wrinkle and lose its rigidity, and over time it shrank. Bromelain enzyme is a protease enzyme which has the same working power as renin (renet), papain and fisin which has the property of hydrolyzing proteins [5]. Hydrolysis that occurs with protease enzymes is caused by breaking peptide bonds from substrate bonds [10].…”
Section: Introductionmentioning
confidence: 99%